High entropy alloy reinforcement for superior electromagnetic interference shielding performance in carbon fiber-reinforced polymer composites - Kucukelyas, Burak; Kaykilarli, Cantekin; Eken, Taha Yasin; Erbas, Ugur; Tabakcioglu, Mehmet Baris (Wiley, 2025)
This study explores the enhancement of electromagnetic interference (EMI) shielding effectiveness (SE) in carbon fiber-reinforced polymer (CFRP) composites through the integration of equatomic CoCuFeNi high entropy alloy (HEA) particles. Employing mechanical alloying (MA), CoCuFeNi HEA powders were synthesized, revealing a face-centered cubic structure with crystallite and particle sizes of 14.7 nm and 11.62 mu m, respectively. The integration of these HEA particles at concentrations of 5%, 10%, and 15% by weight into epoxy resin, followed by the fabrication of composites using the hand lay-up technique. Detailed structural analysis of HEA particles confirmed the successful synthesis of equatomic HEAs via MA. Structural analysis of the HEA integrated composites revealed vacancy regions at 5% concentration, a uniform distribution at 10%, and particle agglomeration causing inhomogeneity and vacancies at 15%. The composites demonstrated significant improvements in EMI SE, with the 10% HEA sample showing superior performance compared to the other samples. Specifically, the 10% HEA composite achieved a peak SE of 73.09 dB at 4.72 GHz, attributed to the optimized distribution of HEA particles that enhanced electrical conductivity and reflective properties.Highlights CoCuFeNi HEA particles were successfully synthesized via MA. HEA particles were added to epoxy at 5, 10, and 15 wt% for composite fabrication. Voids were observed in HEA5, uniformity in HEA10, and clustering in HEA15. EMI shielding was assessed using VNA, SE, dielectric permittivity, and magnetic permeability. The HEA10 composite achieved peak EMI shielding, 73.09 dB at 4.72 GHz.
Keywords: CFRP; electromagnetic interference shielding effectiveness; high entropy alloys; reflection; transmitted waves